Lao People's Democratic Republic : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2015)
This 2014 Article IV Consultation highlights that the real GDP growth of Lao People's Democratic Republic is expected to moderate from 8 percent in 2013 to 7.5 percent in 2014. Domestic activity has slowed, and credit growth has declined from excessive levels. Inflation has declined to 3 percent from 6.5 percent at end-2013, largely owing to weaker food and fuel price momentum. To address vulnerabilities, Executive Directors have emphasized the need for continued fiscal consolidation, greater exchange rate flexibility, tighter monetary conditions, strengthened financial supervision, and improved bank resolution and crisis prevention frameworks.